Associações entre rating de crédito e estrutura de capitais de empresas listadas na América Latina - Silva, Dany Rogers (2012)
A credit rating of low (or high) risk enables a reduction (or increase) the spread paid by the issuer at the time of issuance of credit, as well as in capturing financing and bank lendings. So, the rating appears as a relevant aspect in the decisions of the capital structure of a company, mostly for the possibility of influencing on their levels of debt. However, despite the importance given by the market players and the existence of empirical evidence of the effect of the rating about the capital structure of a company, the few existing studies on the associations between trends of reclassifications of credit ratings and decisions on structure of capital of a firm does not has approached the Latin American markets. In markets of Latin America are not common studies showing that companies internally evaluate the imminence of a reclassification about their rating and, from this, alter the composition of the capital structure so as to avoid causing a downgrade, or even to stimulate the occurrence of an upgrade, in their credit risk classification. Accordingly, the purpose of this research is to analyze the impact of trends in the credit rating reclassifications about decisions structure of capital of listed companies in Latin America. To verify the existence of this association were applied data belonging to all non-financial listed companies in Latin America, possessors of ratings issued by the three major international rating agencies (i.e. Stardand & Poor´s, Moody´s and Fitch) in January 2010. In this way, took part in the research all listed companies in six different Latin American countries, in the period 2001-2010. The main empirical results suggest that: (i) reclassifications of credit ratings have no informational content for the decisions of the capital structure of listed companies in Latin America, in other words, no association was observed between trends of reclassifications credit rating and decisions about the composition of the capital structure of listed companies in Latin America; (ii) between companies considered in the survey, those that were in worst levels of risk and the imminent reclassification of credit rating, tended to use more debt than other companies analyzed in this research.